Intergenerational income mobility: Equality of opportunity a comparison of East and West Germany - Falay, Berna (İstanbul Bilgi Üniversitesi, 2007)
Bu çalısmada kusaklararası gelir hareketliliğinin Doğu ve Batı Almanya datasıkullanılarak karsılastırmalı analizi yapıldı. Gelir hareketliliği, fırsat esitliği ve toplumrefahı açısından incelendi. Bu anlayısı kullanan iki kısmi sıralama kullanıldı. Bunlardanbiri Benabou-Ok sıralaması, diğeriyse Atkinson-Dardanoni sıralamasıdır. Almanya datası1992-2005 aralığındaki baba-oğul ikililerini kapsar. Bu çalısmanın sonucunda, öncekiçalısmalardan farklı olarak Batı Almanya erkek çocuklarının Doğu Almanya’da ki erkekçocuklarından daha esit fırsatlarla karsılasmakta olduğu ve gelirlerini uzun zamandaesitlendiği gösterildi.

This paper examines the intergenerational income mobility in East and West Germanyafter reunification. Mobility is viewed as an opportunity equalizing and welfareenhancing concept. The two relevant partial orderings are used to evaluate theseapproaches, both are defined and used for the analysis of the data. The data consists offather-son pairs from panel data between the years 1992 and 2005. Size transitionmatrices are used for the results and they show that the Western states have a betteropportunity equalizing income mobility process compared to the Eastern states accordingto Benabou-Ok ordering. In addition, it reveals that the West Germany mobility pattern ismore welfare enhancing than the East Germany according to Atkinson-Dardanoniordering.
Kuşaklararası fırsat eşitliği: Doğu ve Batı Almanya karşılastırması